Respuesta :

bcalle
7(x - 4) - 3(x + 5)
Distribute the 7 and 3
7x - 28 - 3x - 15
4x - 43

Answer:

4x-43

Step-by-step explanation:

Here we have to simplify the expression 7(x – 4) – 3(x + 5)

In order to do so we first open the two brackets using distributive laws.

7(x – 4) – 3(x + 5)= 7*x-7*4-3*x-3*5

= 7x-28-3x-15

Now we bring the terms containing the x together and the terms not containing x together

= 7x-3x-28-15

we simplify them

= 4x-43

Hence

7(x – 4) – 3(x + 5)=4x-43 is the simplified expression

ACCESS MORE